Cancer at sea: a case-control study among male Finnish seafarers. Issue 9 (1st September 2002) - Saarni, H; Pentti, J; Pukkala, E
Abstract : Aims: To study the possible work related reasons for the increased incidence of many cancers among seafarers. Methods: A case-control study, nested in a cohort of all male seafarers (n = 30 940) who, according to the files of the Seamen's Pension Fund, had worked on board Finnish ships for any time during the period 1960–80. Cases of cancer of the lung, nervous system, kidney, and pancreas, leukaemia, lymphoma, and all cases histologically defined as mesotheliomas were identified from the Finnish Cancer Registry in 1967–92. The preceding numbers of years at sea in various occupational categories were collected according to the type of ship (dry cargo ship, tanker, passenger vessel, icebreaker, other vessel). Results: The incidence for lung cancer among engine crew increased with the increase in employment time, the odds ratio (OR) after three years being 1.68 (95% CI 1.17 to 2.41). The OR of lung cancer for deck officers was 0.42 (95% CI 0.29 to 0.61). Deck personnel on icebreakers had a significantly increased risk of lung cancer ≥20 years after first employment (OR 3.41, 95% CI 1.23 to 9.49). The OR for mesothelioma among engine crew with a latency of 20 years was 9.75 (95% CI 1.88 to 50.6). The OR for renal cancer among deck officers after three years employment was 2.15 (95% CI 1.14 to 4.08), but there was no increase by employment time or by latency. A rise of OR for lymphoma was detected among deck personnel on tankers, if the employment had lasted over three years (OR 2.78, 95% CI 0.98 to 7.92). The risk pattern for leukaemia was similar to that of lymphoma, the OR among deck personnel on tankers varying from 2.26 (95% CI 1.01 to 5.06) to 6.86 (95% CI 1.62 to 28.8) depending on the length of employment. Conclusions: Results indicate that occupational exposures of deck crews on tankers add to their risk of renal cancer, leukaemia, and possibly lymphoma. Engine crews have an asbestos related risk of mesothelioma, and the engine room conditions also seem to increase risk of lung cancer.